2001
DOI: 10.1177/0310057x0102900412
|View full text |Cite
|
Sign up to set email alerts
|

Intrahospital Transport of Critically Ill Patients: Complications and Difficulties

Abstract: An audit of 97 intrahospital transports of critically ill patients was undertaken within Westmead Hospital. The aims of this audit were to assess all factors that may lead to problems during intrahospital transports. At the completion of a transport medical staff were asked to provide information about their patient and their treatment, as well as any difficulties they may have encountered. Overall, 62% of transports reported some difficulty or complication. Of these, 31% were patient-related and 45% were rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
1
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 21 publications
5
118
1
9
Order By: Relevance
“…This could explain the significant increase of critical incidents in emergency transports in our sample. Interestingly, Smith et al found the opposite in a smaller investigation of 125 transports [5] and Lovell et al did not observe any difference in the incidence of complications between emergency and elective transfers [8].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This could explain the significant increase of critical incidents in emergency transports in our sample. Interestingly, Smith et al found the opposite in a smaller investigation of 125 transports [5] and Lovell et al did not observe any difference in the incidence of complications between emergency and elective transfers [8].…”
Section: Discussionmentioning
confidence: 93%
“…The rate of critical incidents was 4.2% (Tables 3 and 5). Historic rates of critical incidents ranged between 8.1% [16] and 21.4% [15] but comparison with recent rates is difficult as critical incidents are often included in broader categories of complications [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Komplikationen an Schnittstellen können somit auch in Fehler aus beiden Bereichen eingeteilt werden. Bis zu 70% der unerwünschten Zwischenfäl-le entwickeln sich interessanterweise bei innerklinischen Schnittstellen [5,6]. Diese umfassen neben pathophysiologischen Veränderungen auch geräteassoziierte Komplikationen [7,8,9,10].…”
Section: » Jeder Versorgungsabschnitt Produziert Weiterzugebende Infounclassified
“…The technologies used and the interventions performed to these physiologically fragile patients outside of a highly monitored environment potentially threaten their safety. Studies have reported incidents in up to 70% of transports (Lovell et al, 2001;Waydhas, 1999;Zuchelo and Chiavone, 2009). Different categories of incidents have been identified, such as equipment failure, clinical deterioration, inadequate monitoring and incorrect set-up of equipment, inadequate communications, as well as prolonged hospital stay (Beckman et al, 2004;Braman et al, 1987;Caruana and Culp, 1998;Day, 2010;Hurst et al, 1992;Kalish et al, 1995;Lanher et al, 2007;Ligtenburg et al, 2005;Link et al, 1990;Lovell et al, 2001;Mazza et al, 2008;Shirley and Stott, 2001;Smith et al, 1990;Szem et al, 1995;Waydhas, 1999;Waydhas et al, 1995;Zuchelo and Chiavone, 2009).…”
Section: Introductionmentioning
confidence: 99%